2017
DOI: 10.1016/j.cub.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Effects of Recent History on Perception and Decision

Abstract: Recent studies claim that visual perception of stimulus features, such as orientation, numerosity, and faces, is systematically biased toward visual input from the immediate past [1-3]. However, the extent to which these positive biases truly reflect changes in perception rather than changes in post-perceptual processes is unclear [4, 5]. In the current study we sought to disentangle perceptual and decisional biases in visual perception. We found that post-perceptual decisions about orientation were indeed sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

99
662
16

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 365 publications
(777 citation statements)
references
References 38 publications
99
662
16
Order By: Relevance
“…Beyond orientation Fritsche et al, 2017;Liberman, Zhang, & Whitney, 2016;Manassi et al, 2017) and other basic features (motion: Alais, Leung, & Van der Burg, 2017;position: Manassi et al, 2018), serial dependence occurs at higher levels of perception as well. We have recently demonstrated that the continuity field is objectselective by showing that the perception of face identity is systematically biased towards identities seen up to several seconds prior, even across changes in viewpoint (Liberman et al, 2014; see also Taubert, Alais, & Burr, 2016;Taubert, Van der Burg, & Alais, 2016;Xia et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond orientation Fritsche et al, 2017;Liberman, Zhang, & Whitney, 2016;Manassi et al, 2017) and other basic features (motion: Alais, Leung, & Van der Burg, 2017;position: Manassi et al, 2018), serial dependence occurs at higher levels of perception as well. We have recently demonstrated that the continuity field is objectselective by showing that the perception of face identity is systematically biased towards identities seen up to several seconds prior, even across changes in viewpoint (Liberman et al, 2014; see also Taubert, Alais, & Burr, 2016;Taubert, Van der Burg, & Alais, 2016;Xia et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the perception of orientation, numerosity, and other low-level stimulus features is serially dependent-systematically biased (i.e., pulled) towards similar visual input from the recent past (Cicchini, Anobile, & Burr, 2014;Corbett, Fischer, &Taubert, Alais, & Burr, 2016;Xia, Leib, & Whitney, 2016), as well as in feature space (object similarity; Fritsche, Mostert, & de Lange, 2017;Liberman, Fischer, & Whitney, 2014;Manassi, Liberman, Chaney, & Whitney, 2017). The spatio-temporal region over which current object features, such as orientation, are pulled by previously seen features is known as the Continuity Field (CF).…”
Section: Introductionmentioning
confidence: 99%
“…Such a direct perceptual comparison minimizes the influence of working memory and post-perceptual decisions (Fritsche et al, 2017;Schneider & Komlos, 2008) and thus could shed light on the perceptual nature of the reference repulsion bias. To investigate whether discrimination judgments would alter the perceived orientation of a stimulus we computed biases between bins of trials with opposite and correct boundary judgments.…”
Section: Cc-by-nc-ndmentioning
confidence: 99%
“…http://dx.doi.org/10.1101/366393 doi: bioRxiv preprint first posted online Jul. 10, 2018; 2018; Bliss et al, 2017;Fritsche et al, 2017;Papadimitriou et al 2015). Furthermore, the postperceptual nature of this repulsive bias away from an external reference delineates the effect from repulsive perceptual biases away from cardinal orientations, which may act as internal references (Rauber & Treue, 1998;Tomassini, Morgan & Solomon, 2010;Wei & Stocker, 2015).…”
Section: Cc-by-nc-ndmentioning
confidence: 99%
See 1 more Smart Citation